Pengembangan Media Interaktif pada Materi Menulis Teks Puisi Siswa Kelas X SMA Al-Washliyah Pasar Senen Medan - Fachry Zain (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
The purpose of this study was to find out how the development of interactive media, the feasibility of interactive media in writing poetry text materials to increase the motivation of the students of class X of SMA Al-Washliyah Pasar Senen Medan. This research is a type of research and development using Borg and Gall development model. The steps taken in this development research are: research and collection, planning, draft or product development, initial field trials, revising test results, field trials, final product improvements. The population and the research sample were 23 students. The results showed that the product development was declared feasible based on the results showed that that material expert I gets the “Eligible” score criteria with a percentage (80%) and the material expert II gets the “Enough Eligible” criteria (64%), the results of the media expert assessment I gets the value criteria “Very Eligible” with a percentage (86%) and media expert II gets the criteria for “Eligible” with a percentage (80%). Field implementation test with 23 students of class X SMA Al-Washliyah Pasar Senen Medan gets the criteria of “Very Eligible” with a percentage (90%) and the terachers gets the criteria of “Very Eligible” with a percentage (94%).